1991
DOI: 10.4141/cjas91-039
|View full text |Cite
|
Sign up to set email alerts
|

The effect of castration age, method and implant regime on growth and carcass traits of male beef cattle

Abstract: 1984-1985 and 1985-1986

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…These results agree with previous data in reports on heifers (Cohen et al 1987) and steers (Cohen et al 1991) and support their conclusion that zeranol contributes to increased protein deposition. The results reported in the present study are of added interest.…”
supporting
confidence: 93%
“…These results agree with previous data in reports on heifers (Cohen et al 1987) and steers (Cohen et al 1991) and support their conclusion that zeranol contributes to increased protein deposition. The results reported in the present study are of added interest.…”
supporting
confidence: 93%
“…Investigations performed by Bagley et al [6], Cohen et al [ 10] and Gregory and Ford [IS] led to similar results.…”
Section: Endocrine Assaysmentioning
confidence: 53%
“…Conversely, LM area was greater ( P < 0.01) in BUL (101.3 cm 2 ) and INJ (98.1 cm 2 ) than BAN (87.7 cm 2 ). Cohen et al (1991) reported adjusted LM area of bulls was greater compared to surgical castrates and also greater compared with chemically castrated (lactic acid) cattle in 1 yr of a 2-yr study. Longissimus muscle area is highly correlated to carcass weight ( Greiner et al, 2003 ), which is supported by the present study; however, BAN cattle were not implanted with analogues of testosterone as per standard industry practices, which presumably would have increased both HCW and LM area.…”
Section: Resultsmentioning
confidence: 86%
“…In the companion manuscript, Ball et al (2018) reported greater final BW in INJ and BUL compared with BAN. Previous research in chemically (lactic acid) castrated bulls reported that intact bulls had greater HCW compared with chemically castrated cattle ( Cohen et al, 1991 ). Similarities in HCW between INJ and BUL correlates with similarly increased serum testosterone concentrations in INJ and BUL compared with BAN ( Ball et al, 2018 ) and was phenotypically confirmed via noticeably increased male characteristics possessed by both INJ and BUL treatments.…”
Section: Resultsmentioning
confidence: 93%